2005
DOI: 10.4049/jimmunol.174.3.1205
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Controls MHC Class II-Mediated Antigen Presentation by Epithelial Cells In Vivo

Abstract: Epithelial cells at environmental interfaces provide protection from potentially harmful agents, including pathogens. In addition to serving as a physical barrier and producing soluble mediators of immunity, such as cytokines or antimicrobial peptides, these cells are thought to function as nonprofessional APCs. In this regard, intestinal epithelial cells are particularly prominent because they express MHC class II molecules at the site of massive antigenic exposure. However, unlike bone marrow-derived profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 42 publications
2
78
0
Order By: Relevance
“…Therefore, its localisation in the lung may pinpoint to an important function for cathepsin S. Thus, cathepsin S is also expressed in antigen-presenting cells (APC), such as macrophages and dendritic cells, and in MHC Class II cells, and could mediate CD4 + T-cell mediated immune responses. In addition, it is expressed in non-professional APCs, such as epithelial cells (12)(13)(14). Such distribution strongly suggests a role for cathepsin S in immune and inflammatory processes such that provoked by ozone exposure.…”
Section: Role Of Cathepsin S In Ozone-induced Airway Hyperresponsivenmentioning
confidence: 99%
“…Therefore, its localisation in the lung may pinpoint to an important function for cathepsin S. Thus, cathepsin S is also expressed in antigen-presenting cells (APC), such as macrophages and dendritic cells, and in MHC Class II cells, and could mediate CD4 + T-cell mediated immune responses. In addition, it is expressed in non-professional APCs, such as epithelial cells (12)(13)(14). Such distribution strongly suggests a role for cathepsin S in immune and inflammatory processes such that provoked by ozone exposure.…”
Section: Role Of Cathepsin S In Ozone-induced Airway Hyperresponsivenmentioning
confidence: 99%
“…Several lines of more convincing evidence support the idea that MHCII peptide loading occurs at the endosomal-delimiting membrane, in contrast to ILVs. First, MHCII failed to sort to ILVs in cathepsin-S-deficient intestinal epithelial or professional antigen-presenting cells (Beers et al 2005;Boes et al 2005). Cathepsin S is required for the degradation of Ii ( p10), and hence also for subsequent ubiquitination of MHCII (see above).…”
Section: Mvb Dynamics and Mhcii Peptide Loadingmentioning
confidence: 99%
“…A range of epithelial dysfunctions have been implicated in the pathogenesis of CF lung disease, which are ultimately consequences of mutations in the CF transmembrane conductance regulator (CFTR) gene. Given that epithelial cells have been reported to express CTSS (21,24,25), we investigated the hypothesis that CF airway epithelial cells contribute to the protease burden of the CF lung by releasing increased levels of CTSS compared with non-CF control cells, and explore the mechanism responsible for our observations. Some of the results of these studies have been previously reported in the form of abstracts (26,27).…”
mentioning
confidence: 99%
“…In contrast to other cysteine cathepsin isoforms, CTSS can retain proteolytic activity after prolonged exposure to neutral pH in the extracellular environment, where it retains nearly as much elastase activity as NE (17)(18)(19)(20). Consequently, in addition to pivotal roles in cellular events, such as antigen processing (21), CTSS has the capacity to promote remodeling of the extracellular matrix via its potent elastinolytic activity. A recent report demonstrated the ability of CTSS to activate the epithelial sodium channel, which may be pathophysiologically relevant in inflammatory diseases, such as CF (22).…”
mentioning
confidence: 99%